THE INFLUENCE OF PHISICAL EDUCATIN ON DEVOLPEMENT OF ABILITIES OF ELDERLY SCHOOLCHILDREN - Veroljub Stanković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2009)
On specimen of schoolchildren of primary school in Serbia, was done a research of physical education influence on developing of motoric abilities. Population, on which was extracted a specimen, were samples of eight class, urban female with regular physi- cal education class. Based on selected statistical model and program, aims and suspen- ded hypothesis, was decided that specimen includes 80 samples. Specimen of motoric variables included 18 tests that were used to esteem explosive and repetitive strength, force, sprint and segment speed, flexibility, balance, precision and coordination. The results of canonic discriminative variable analyzed for estimation of motoric abilities, shows that tested schoolchildren on the end of class in one school year, are statistically different in tested abilities. Analyzing the validity of obtained results, can be concluded that between first and second group exists the connection of discriminative functions. The significant difference between groups was presented with Wilks lambda test, tested over Bartlet X2 test, which is (21.78). Applied experimental procedure showed that phisi- cal educatin class contributes to high rate of motoric abylities.